Optoelectronic properties of infrared rapid-thermal-annealed SnOx thin films. Issue 10 (December 2015) - Jiang, Yu-Hao; Kao, Peng-Kai; He, Jyun-Ci; Chiu, I-Chung; Yang, Yao-Jhen; Wu, Yu-Han; Hsu, Cheng-Che; Cheng, I-Chun; Chen, Jian-Zhang
Abstract: We investigated rf-sputtered SnO x thin films after thermal oxidation in ambient air at 245 °C (below the temperature for the disproportionation reaction 2SnO→Sn+SnO2 ) using an infrared rapid heating furnace. The most significant changes occur during the initial 2.5 min of thermal annealing. The amorphous as-deposited film rapidly crystallized with metallic Sn and SnO phases as identified by XRD after thermal annealing. Both EPMA and XPS indicate decreasing [Sn]/[O] ratios after the initial 2.5 min of annealing, suggesting the occurrence of an oxidation process that is hindered for longer annealing durations. The lower [Sn]/[O] ratio identified by XPS than by EPMA suggests more severe oxidation at the surface. Thermal oxidation improves the transmittance and increases the band gap from 1.80 to 2.79 eV. The annealed films exhibit resistivity of ~16 Ω cm, hall mobility of ~0.6 cm 2  V −1  s −1, and carrier concentration of ~7×10 17  cm −3 . Both Hall and Seebeck coefficient measurements confirm p-type conductivity for all annealed films.